Factor XIII expression within aortic valves and its plasma activity in patients with aortic stenosis: association with severity of disease - Kapusta, Przemyslaw; Wypasek, Ewa; Natorska, Joanna; Grudzien, Grzegorz; Sobczyk, Dorota; Sadowski, Jerzy; Undas, Anetta (Thrombosis and Haemostasis, 2012)
Aortic valve stenosis (AS) shares several similarities with atherosclerosis. Factor XIII (FXIII) has been detected within atherosclerotic plaques and may contribute to the development of atherosclerosis via multiple mechanisms. In the current study, we sought to investigate FXIII expression within human stenotic aortic valves and its association with severity of the disease. We prospectively enrolled 91 consecutive patients with AS scheduled for isolated valve replacement. Valvular FXIII subunit A (FXIII-A), fibrin and macrophages expression was evaluated by immunostaining. FXIII-A subunit transcripts and FXIII-A Val34Leu polymorphism was determined by real-time PCR. Plasma FXIII (pFXIII) activity was measured. We demonstrated that the valvular FXIII-A was predominantly expressed on the aortic side of leaflets, colocalized with alternatively activated macrophages (AAM). Areas stained for FXIII-A showed positive correlations with valvular fibrin presence, degree of calcification, pFXIII activity and the severity of AS, reflected by mean and maximum transvalvular gradients (all, p<0.001). The FXIII-A mRNA in the stenotic leaflets was significantly elevated compared to control leaflets. Interestingly, pFXIII activity was also positively correlated with mean (p<0.001) and maximum (p=0.001) transvalvular gradient. The FXIII-A Val34Leu polymorphism did not affect FXIII-A and fibrin expression in AS valves. In conclusion, the study is the first to show abundant expression of FXIII-A at the mRNA and protein levels within human stenotic aortic valves, which is associated with the severity of AS. Our findings might suggest that FXIII in the stenotic valves is presented in AAM and may be involved in the AS progression.
Keywords: Aortic valve stenosis; Calcification; factor XIII; alternatively activated macrophages